1995
DOI: 10.1016/0092-8674(95)90167-1
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of clathrin assembly and trimerization defined using recombinant triskelion hubs

Abstract: Clathrin polymerization into a polyhedral vesicle coat drives receptor sorting at cellular membranes during endocytosis and organelle biogenesis. To study clathrin self-assembly, we expressed the C-terminal third of the clathrin heavy chain in bacteria. The recombinant fragment trimerized, bound clathrin light chains, and morphologically resembled the hub domain of the triskelion-shaped clathrin molecule. Self-assembly of recombinant hubs demonstrated a regulatory role for clathrin light chains and for the dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
250
1
3

Year Published

1996
1996
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 153 publications
(269 citation statements)
references
References 40 publications
15
250
1
3
Order By: Relevance
“…120 nm in diameter), suggesting that, beyond a certain point, a conformation-linked unfavorable energy term may start to overwhelm favorable interaction energy gained because of the association of the clathrin legs (7,26). The fact that these might be mechanical in nature is suggested by the fact that large reconstituted clathrin structures are observed only when the triskelia lack distal segments, in which case leg bending is suppressed and large, essentially flat, structures are observed (27).…”
Section: Summary and Discussionmentioning
confidence: 99%
“…120 nm in diameter), suggesting that, beyond a certain point, a conformation-linked unfavorable energy term may start to overwhelm favorable interaction energy gained because of the association of the clathrin legs (7,26). The fact that these might be mechanical in nature is suggested by the fact that large reconstituted clathrin structures are observed only when the triskelia lack distal segments, in which case leg bending is suppressed and large, essentially flat, structures are observed (27).…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Bovine hub fragment with an N-terminal His tag and bovine brain LCb were prepared as described previously (23). Protein concentration was determined by Bradford assays (Bio-Rad).…”
Section: Methodsmentioning
confidence: 99%
“…Mouse Hip1R cDNA, provided by David Drubin, University of California, Berkeley, was amplified and cloned into the SalI site of pGBT9 or the BamHI/XhoI sites of pACT2. HC fragments were amplified from bovine brain cDNAs (23) and cloned into the BamHI-SalI sites of pGBT9 (Clontech). Rat AP2 ␤-hinge ear (616 -937) was amplified (24) and cloned into the SmaI/XhoI sites of pACT2.…”
Section: Methodsmentioning
confidence: 99%
“…The expression of the C-terminal third of the clathrin heavy chain, also known as the clathrin hub, inhibits CCV formation and, thus, clathrin-mediated transport events (Liu et al, 1995(Liu et al, , 1998Dhonukshe et al, 2007). It was recently shown that expression of a fluorescently tagged clathrin hub (green fluorescent protein [GFP]-Hub1) in Arabidopsis protoplasts inhibits the endocytic uptake of the amphiphilic styryl dye FM4-64 (Dhonukshe et al, 2007).…”
Section: Gfp-hub1 Inhibits Endocytosis But Not Transport To the Lyticmentioning
confidence: 99%